1986
DOI: 10.1111/j.1432-1033.1986.tb09909.x
|View full text |Cite
|
Sign up to set email alerts
|

The mouse myoglobin gene

Abstract: Seal myoglobin (Mb) exons 1 and 3 were used as probes to isolate the functional mouse Mb gene. This gene has a very low level of Mb expression in skeletal muscle. Although it is shorter, the mouse Mb gene displays the common organisation found in human and seal Mb genes. In addition, we have defined blocks of conserved sequences in the 5′ flanking region by comparison with other mammalian Mb genes. Moreover, about 103 bases upstream of the cap site we identified a repetitive B1 element directly associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Teleost Mb is comprised of 146 amino acids (23), with an apparent molecular size of approximately 16 kDa. The more slowly migrating human Mb with a molecular size of 17.8 kDa contains 153 amino acids and is typical of mammalian Mbs (24,25). Heart ventricles of the notothenioid species contained a 0.9-kb mRNA (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Teleost Mb is comprised of 146 amino acids (23), with an apparent molecular size of approximately 16 kDa. The more slowly migrating human Mb with a molecular size of 17.8 kDa contains 153 amino acids and is typical of mammalian Mbs (24,25). Heart ventricles of the notothenioid species contained a 0.9-kb mRNA (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The murine aldolase A pM-derived mRNAs (M-mRNA)-specific probe corresponds to the M-specific exon of the mouse aldolase A gene (18). The myoglobin probe was synthesized by reverse transcription-polymerase chain reaction and corresponds to the third exon of the gene (27). MyHC-2B transcripts were detected using a 76-bp fragment of the 3Ј-untranslated region of the rat gene (28); in this case, hybridization was performed at 55°C (in these conditions, there is no cross-hybridization with other MyHC as shown by the absence of signal in soleus (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Myoglobin, cytoglobin and hemoglobin are believed to have shared a common ancestral globin more than 500 million years ago (Burmester et al, 2002). The genomic structure of the myoglobin gene has been extensively studied in a variety of species, including the Grey seal (Halichoerus grypus), human (Homo sapiens), mouse (Mus musculus) and sperm whale (Physeter catodon) (Blanchetot et al, 1986;Weller et al, 1986;Wittenberg and Wittenberg, 1989). These studies have demonstrated a considerable homology among various species in regards to the genomic structure of the myoglobin gene.…”
Section: Myoglobin Genomic Organization and Gene Structurementioning
confidence: 99%
“…O 2 , NO, free radicals, etc.) (Blanchetot et al, 1986). expressed in smooth muscle cells, certain human epithelial cancers and in non-muscle tissues of certain species of fish (Cossins and Berenbrink, 2008;Cossins et al, 2009;Flonta et al, 2009;Fraser et al, 2006;Rayner et al, 2009;Roesner et al, 2006).…”
Section: Myoglobin Genomic Organization and Gene Structurementioning
confidence: 99%